2016
DOI: 10.1002/jcsm.12147
|View full text |Cite
|
Sign up to set email alerts
|

Welcome to the ICD‐10 code for sarcopenia

Abstract: The new ICD‐10‐CM (M62.84) code for sarcopenia represents a major step forward in recognizing sarcopenia as a disease. This should lead to an increase in availability of diagnostic tools and the enthusiasm for pharmacological companies to develop drugs for sarcopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
441
0
33

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 708 publications
(475 citation statements)
references
References 76 publications
1
441
0
33
Order By: Relevance
“…Sarcopenia is becoming a major health issue with the aging of the world's population [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia is becoming a major health issue with the aging of the world's population [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia is defined as low physical function in persons with a low muscle mass (27)(28)(29)(30). Jones et al (31) reported that sarcopenia was present in 15% of COPD patients.…”
Section: Figure 2 Mechanisms Of Sarcopenia In Persons With Copdmentioning
confidence: 99%
“…It has been proposed that sarcopenia might indeed represent a promising organ-specific pathophysiological background for defining a muscular condition of clinical relevance 11) . In this context, it is noteworthy that the recent allocation of a specific International Statistical Classification of Diseases and Related Health Problems (ICD-10) code to sarcopenia 12) demonstrated how this condition has all the necessary characteristics for theoretically framing a nosological entity. However, the creation of an ICD-10 code for sarcopenia has surely solved part of the issue related to the implementation of the condition in the clinical setting.…”
Section: What Is Sarcopenia?mentioning
confidence: 99%